Determinants of Bank Efficiency: Evidence from Czech Banking Sector - Rostislav Staněk (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2015)
The paper identifies bank-specific determinants of Czech commercial bank efficiency during the period 2000–2012. The paper employs a panel version of a stochastic efficiency frontier model with time variant efficiency to identify the impact of bank size and the structure of bank’s portfolio on the bank’s cost and profit efficiency. The results of the estimation show that bank size has no impact on cost efficiency but it negatively influences the bank’s ability to generate revenue. Cost efficiency increases with deposit-to-assets ratio and profit efficiency increases with loans-to-assets ratio. During the examined period average bank lost one fourth of its profit compared to best-practice bank.